Neuro-behavioural impact of changes in hippocampal neural activity - Williams, Stuart (2021)
Hippocampal metabolic hyperactivity and neural disinhibition, i.e. reduced GABAergic inhibition, have been associated with schizophrenia, although a causal link between disinhibition and metabolic hyperactivity remains to be demonstrated. Regional neural disinhibition might also disrupt neural activation in projection sites, such as the prefrontal cortex and striatum, which may contribute to cognitive impairments and positive symptoms characteristic of schizophrenia. To further examine the brain-wide impact of hippocampal disinhibition and the associated behavioural and cognitive changes, we combined ventral hippocampal infusion of the GABA-A antagonist picrotoxin with translational neural imaging and behavioural methods in rats. First, we used a conditioned emotional response paradigm to assess the impact of hippocampal disinhibition on aversive conditioning and salience modulation in the form of latent inhibition (chapter 2), both of which have been reported to be disrupted in schizophrenia. These experiments demonstrated hippocampal disinhibition caused disrupted cue and contextual fear conditioning, whilst we found no evidence that hippocampal disinhibition affects salience modulation as reflected by latent inhibition of fear conditioning. The disruption of fear conditioning resembles aversive conditioning deficits reported in schizophrenia and may reflect disruption of neural processing at hippocampal projection sites. Second, we used SPECT imaging to map changes in brain-wide activation patterns caused by hippocampal GABA dysfunction (chapter 3). SPECT experiments revealed increased neural activation around the infusion site in the ventral hippocampus, resembling metabolic hippocampal hyperactivity consistently reported in schizophrenia. In contrast, activation in the dorsal hippocampus was significantly reduced. This resembles the finding of anterior hippocampal hyperactivity coupled with reduced posterior hippocampal activation in patients with schizophrenia. Hippocampal disinhibition also caused marked extra-hippocampal activation changes in neocortical and subcortical sites, including sites implicated in fear learning and anxiety such as the medial prefrontal cortex (mPFC), septum, lateral hypothalamus and extended amygdala which may contribute to the disruption of fear conditioning demonstrated in chapter 2. Importantly, increased activation in the mPFC corresponds with previously reported prefrontal-dependent attentional deficits caused by hippocampal disinhibition. Third, to complement these findings we used magnetic resonance spectroscopy (MRS) to determine the effects of hippocampal disinhibition on neuro-metabolites within the mPFC (chapter 4). Using MRS, we demonstrated that hippocampal disinhibition causes metabolic changes in the mPFC, reflected by increased myo-inositol and reduced GABA concentrations.